Simulating Surface and Subsurface Water Balance Changes Due to Burn Severity - Atchley, A.L. (2020)
The reduction of evapotranspiration often dominated the new water balance compared with the increase in overland flow, resulting in higher soil moisture. However, this modeling experiment also identified a tipping point where increased overland flow from high burn severity sites eclipses the effect of reduced evapotranspiration on the water balance, causing comparatively drier post‐fire soils. In particular, high burn severity sites approach a threshold that results in larger changes to overland flow than changes in evapotranspiration, potentially moving the site to an overland flow dominated regime. The shifts in water balance components have implications for how site conditions will change under a range of burn severity scenarios.